First-principles study on surface stability and interface magnetic properties of SmFe12. (13th March 2020) - Ainai, Yuta; Shiozawa, Tomoharu; Tatetsu, Yasutomi; Gohda, Yoshihiro
Abstract: We report the most stable surface of SmFe12 and the interface magnetic properties of SmFe12 with SmCu and bcc Fe as subphases. We find that the (110) surface with the highest exposition of Sm is the most stable surface of SmFe12 . Stabilization by the exposition of rare-earth is also confirmed for Nd2 Fe14 B. Moreover, we also demonstrate that SmCu improves not only magnetic moments and the anisotropy of grain surfaces of SmFe12 but also well suppresses the magnetic interaction between SmFe12 grains.